1963
DOI: 10.1055/s-0038-1654997
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Heparin with Fibrinolysis

Abstract: SummaryHeparin in high concentration inhibits the fibrinolysis of human plasma clots or bovine fibrin by fibrinolytic agents which produce plasminogen activation. Heparin has no effect on the fibrinolytic activity of plasmin or Aspergillus protease.In order to produce inhibition of plasminogen activation heparin requires the presence of a co-factor which is present in citrated human plasma but absent from its euglobulin fraction.In none of the concentrations tested has heparin an enhancing effect on fibrinolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1964
1964
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Thus the 'plasmin' preparation used was a human streptokinase-activated euglobulin now known to owe its fibrinolytic activity chiefly to a plasminogen activator (SK activator), and the heparin samples were later found to be contaminated with an inhibitor [4], The negligible effect of pure heparin preparations on components of the fibrinolytic system (plasmin and activators of plasminogen) is important when the effects of heparin in the body are considered. Our heparin data resemble that obtained by H olem ans et al [9] who studied its effects on the fibrinolytic activities of streptokinase, urokinase, chloroform-activated bo vine plasmin, and aspergillus protease. They did not observe an enhancing effect.…”
Section: Discussionsupporting
confidence: 86%
“…Thus the 'plasmin' preparation used was a human streptokinase-activated euglobulin now known to owe its fibrinolytic activity chiefly to a plasminogen activator (SK activator), and the heparin samples were later found to be contaminated with an inhibitor [4], The negligible effect of pure heparin preparations on components of the fibrinolytic system (plasmin and activators of plasminogen) is important when the effects of heparin in the body are considered. Our heparin data resemble that obtained by H olem ans et al [9] who studied its effects on the fibrinolytic activities of streptokinase, urokinase, chloroform-activated bo vine plasmin, and aspergillus protease. They did not observe an enhancing effect.…”
Section: Discussionsupporting
confidence: 86%
“…Olesen (334) suggested that the fibrinolysis is caused by plasminogen activation. However, Holemans et al (335) found that the presence of a cofactor is necessary. Heparin is known also to accelerate catalytically the neutralization of thrombin by antithrombin 111 and thus prevent reclotting following fibrinolysis (336).…”
Section: Pharmacologymentioning
confidence: 99%
“…In vitro studies on the influence of heparin on fibrin olysis revealed contradictory results. Some authors have presented evidence that fibrinolysis is enhanced by heparin [14,15], some have described an inhibitory effect on fibrinolysis induced by plasminogen activators [1,4,5]. In animal experiments, heparin was shown to cause partial lysis of experi mentally produced thrombi [12,13], In human blood samples accelerated clot lysis was reported following intravenous administration of heparin [6],…”
mentioning
confidence: 99%